Konsep Pemanen Air Hujan (Rainwater Harvesting) sebagai Alternatif Sumber Daya Air Bersih di Kampung Lakkang Kota Makassar - Ratih Nisrina Pratiwi R. Djalle; Yashinta Kumala Dewi Sutopo; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2022)
Rainwater harvesting is a system of collecting and storing rainwater for reuse in daily activities. This concept can be applied to the research location because rainwater that falls to the surface cannot be accommodated optimally on land. This study aims to determine the operating system of the installation and maintenance of rainwater harvesting techniques, evaluate the potential applications of rainwater harvesting, and provide guidance on the concept of rainwater harvesting. This research is a descriptive research with a quantitative approach. This research was conducted from March to November 2020 (8 months). The method of collecting data is carried out primarily through observation, field surveys, and observation of building functions. The secondary data obtained through literature studies and government agency data. The analysis used is a synthesis of literature, the potential per building, the amount of rainwater that can be harvested, and the amount of household/domestic water demand. The results of this study indicate that the application of this concept can meet the needs of water and is able to become an alternative in meeting the needs of clean water in the research location. The potential for rainwater harvesting based on the calculation results is 58,099,680 liters/day or if it is assumed that each house has the same roof area. So each house can accommodate rain water of 272,768 liters/day/house. This figure is obtained through rainwater that can be harvested in Kampung Lakkang divided by the number of houses, namely 213 houses. The number of household/domestic water needs shows 58620 liters/day, with an average for each house of 300 liters/day.